Selenium supplementation and pregnancy outcomes - Dahlen, Carl R.; Reynolds, Lawrence P.; Caton, Joel S. (Frontiers in Nutrition, 2022)
In vertebrates and invertebrates, selenium (Se) is an essential micronutrient, and Se deficiency or excess is associated with gonadal insufficiency and gamete dysfunction in both males and females, leading to implantation failure, altered embryonic development and, ultimately, infertility. During pregnancy, Se excess or deficiency is associated with miscarriage, pre-eclampsia (hypertension of pregnancy), gestational diabetes, fetal growth restriction and preterm birth. None of this is surprising, as Se is present in high concentrations in the ovary and testes, and work in animal models has shown that addition of Se to culture media improves embryo development and survival in vitro in association with reduced reactive oxygen species and less DNA damage. Selenium also affects uterine function and conceptus growth and gene expression, again in association with its antioxidant properties. Similarly, Se improves testicular function including sperm count, morphology and motility, and fertility. In animal models, supplementation of Se in the maternal diet during early pregnancy improves fetal substrate supply and alters fetal somatic and organ growth. Supplementation of Se throughout pregnancy in cows and sheep that are receiving an inadequate or excess dietary intake affected maternal whole-body and organ growth and vascular development, and also affected expression of angiogenic factors in maternal and fetal organs. Supplemental Se throughout pregnancy also affected placental growth, which may partly explain its effects on fetal growth and development, and also affected mammary gland development, colostrum yield and composition as well as postnatal development of the offspring. In conclusion, Se supplementation in nutritionally compromised pregnancies can potentially improve fertility and pregnancy outcomes, and thereby improve postnatal growth and development. Future research efforts should examine in more detail and more species the potential benefits of Se supplementation to reproductive processes in mammals.